2008
DOI: 10.1136/bjsm.2008.050534
|View full text |Cite
|
Sign up to set email alerts
|

Sudden cardiac arrest in children and young athletes: the importance of a detailed personal and family history in the pre-participation evaluation

Abstract: Healthcare providers have become more aware of and concerned about paediatric sudden cardiac arrest. The diseases predisposing a patient to sudden cardiac arrest are all infrequently encountered. However, a detailed and comprehensive patient and family history may reveal warning signs and symptoms that identify a patient at higher risk for sudden cardiac arrest. Since many of these diseases are genetic, extensive family evaluation may uncover a previously undetected cardiac disease process and as well direct t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 55 publications
0
16
0
4
Order By: Relevance
“…Retrospective reviews performed following an athlete's sudden death found that between 10% and 53% of victims had a possibly related cardiovascular disease or early death in their family. 12 The autosomaldominant pattern of inheritance of most hereditary heart diseases may explain this observation, because these disorders are often inherited from a parent and may have been present in a family for generations. 13 However, even following the most comprehensive review of an athlete's family history, certain features of inherited cardiovascular diseases preclude a clinician from easily recognizing the risk of disease, even if it truly exists in the family (Box 1).…”
Section: Using Family History To Identify Athletes At Risk For Suddenmentioning
confidence: 97%
“…Retrospective reviews performed following an athlete's sudden death found that between 10% and 53% of victims had a possibly related cardiovascular disease or early death in their family. 12 The autosomaldominant pattern of inheritance of most hereditary heart diseases may explain this observation, because these disorders are often inherited from a parent and may have been present in a family for generations. 13 However, even following the most comprehensive review of an athlete's family history, certain features of inherited cardiovascular diseases preclude a clinician from easily recognizing the risk of disease, even if it truly exists in the family (Box 1).…”
Section: Using Family History To Identify Athletes At Risk For Suddenmentioning
confidence: 97%
“…The reader is directed to reference texts and previous publications for more detail about each of these individual conditions. 14,15 …”
Section: Cardiac Disorders Predisposing Youth To Scamentioning
confidence: 99%
“…The most efficient and effective venue is also unclear. Rather than creating specific screening clinics, it may be a consideration to first use a 'casefinding' approach that uses the expertise of the primary care physicians who ideally have access to longitudinal clinical follow-up data, a thorough family history and a relationship with the individual, which would facilitate information gathering and sharing, and the opportunity for diagnosis (2,35). • There will be a significant false-positive rate • There will be an important false-negative rate…”
Section: Conclusion and Considerationsmentioning
confidence: 99%